Mitochondrial activity in the frontal cortex area 8 and angular gyrus in Parkinson's disease and Parkinson's disease with dementia. (16th March 2017) - Garcia‐Esparcia, Paula; Koneti, Anusha; Rodríguez‐Oroz, M. Cruz; Gago, Belen; del Rio, José Antonio; Ferrer, Isidro
Abstract: Altered mitochondrial function is characteristic in the substantia nigra in Parkinson's disease (PD). Information about mitochondria in other brain regions such as the cerebral cortex is conflicting mainly because most studies have not contemplated the possibility of variable involvement depending on the region, stage of disease progression and clinical symptoms such as the presence or absence of dementia. RT‐qPCR of 18 nuclear mRNAs encoding subunits of mitochondrial complexes and 12 mRNAs encoding energy metabolism‐related enzymes; western blotting of mitochondrial proteins; and analysis of enzymatic activities of complexes I, II, II, IV and V of the respiratory chain were assessed in frontal cortex area 8 and the angular gyrus of middle‐aged individuals (MA), and those with incidental PD (iPD), long‐lasting PD with parkinsonism without dementia (PD) and long‐lasting PD with dementia (PDD). Up‐regulation of several genes was found in frontal cortex area 8 in PD when compared with MA and in the angular gyrus in iPD when compared with MA. Marked down‐regulation of genes encoding mitochondrial subunits and energy metabolism‐related enzymes occurs in frontal cortex but only of genes coding for energy metabolism‐related enzymes in the angular gyrus in PDD. Significant decrease in the protein expression levels of several mitochondrial subunits encoded by these genes occurs in frontal cortex area 8 and angular gyrus in PDD. Moreover, expression of MT‐ND1 which is encoded by mitochondrial DNA is also reduced in PDD. Reduced enzymatic activity of complex III in frontal cortex area 8 and angular gyrus is observed in PD, but dramatic reduction in the activity of complexes I, II, II and IV in both regions characterizes PDD. Dementia in the context of PD is linked to region‐specific deregulation of genomic genes encoding subunits of mitochondrial complexes and to marked reduction in the activity of mitochondrial complexes I, II, III and IV.